Epidemiology of knee injuries among adolescents: a systematic review - Louw, Q. A.; Manilall, J.; Grimmer, K. A. (British Journal of Sports Medicine, 2008)
Background: Youth sports injury is a public health concern, as it has detrimental effects on the health and well-being of young athletes. The knee joint is reported to be the most common joint injured by young sports participants. The potential loss of ability to participate in regular physical activity after injury is alarming, because physical inactivity is one of the major risk factors associated with systemic disease, disability and/or death worldwide.